LIMBAH SAGU: POTENSI LOKAL UNTUK MEDIA PUPUK HAYATI - Reginawanti Hindersah; A. Marthin Kalay; Agus Jacob; Abraham Talahaturuson (Jurnal Agroekoteknologi, 2014)
Sago starch production leaves solid and liquid wastes that has not been used optimally. Both organic substances still contains a lot of nutrients, and could be processed into raw material for bio-fertilizers media. Solid waste, known as ela sago, has been developed into compost while the liquid waste did not. The objective of this study was to verify volume ratio of liquid inoculant of Azotobacter chroococcum in solid inoculant produced from ela sago; and determine the concentration of sago waste water as a growth medium of biofertilizer A. chroococcum. This study confirms population of A.chroocccum and T. harzianum in ela sago compost reached 106 cfu/g and 108 cfu/g consecutively following enrichment with either 2% or 4% of A. chroococcum liquid inoculant. Sago wastewater can used support A.chroococcum growth. This study proved that waste from sago starch production could be used as a natural medium for biofertilizer.